Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1121/10.0001179
|View full text |Cite
|
Sign up to set email alerts
|

Perception of musical melody and rhythm as influenced by native language experience

Abstract: This study used the Musical Ear Test [Wallentin, Nielsen, Friis-Olivarius, Vuust, and Vuust (2010). Learn. Indiv. Diff. 20, 188–196] to compare musical aptitude of native Japanese and Chinese speakers. Although the two groups had similar overall accuracy, they showed significant differences in subtest performance. Specifically, the Chinese speakers outperformed the Japanese counterparts on the melody subtest, but the reverse was observed on the rhythm subtest. Within-group comparisons revealed that Chinese spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 27 publications
5
27
3
Order By: Relevance
“…In the Montreal Battery of Evaluation of Amusia, Mandarin listeners discriminated pitch more accurately than did Dutch listeners (Chen et al, 2016). In the melody subtest of the wellvalidated Musical Ear Test, Mandarin listeners scored higher than Japanese listeners (Zhang et al, 2020). Collectively, the above studies have suggested that speaking a tone language sharpens musical pitch sensitivity.…”
Section: Language-to-music Transfermentioning
confidence: 89%
See 3 more Smart Citations
“…In the Montreal Battery of Evaluation of Amusia, Mandarin listeners discriminated pitch more accurately than did Dutch listeners (Chen et al, 2016). In the melody subtest of the wellvalidated Musical Ear Test, Mandarin listeners scored higher than Japanese listeners (Zhang et al, 2020). Collectively, the above studies have suggested that speaking a tone language sharpens musical pitch sensitivity.…”
Section: Language-to-music Transfermentioning
confidence: 89%
“…This seemed to indicate that although tone language experience enhanced the subcortical processing of musical pitch, this neural enhancement did not yield any behavioral perceptual advantage. However, the results should be interpreted with caution given (a) the small sample size (n = 11 per group) and (b) the preponderance of studies showing that Cantonese/Mandarin non-musicians outperformed Dutch/English/French/Japanese non-musicians on behavioral measures of musical pitch perception (Wong et al, 2012;Asaridou and McQueen, 2013;Bidelman et al, 2013;Chen et al, 2016;Zhang et al, 2020). It remained unclear whether enhanced neural encoding of musical pitch could explain the behavioral advantage on musical pitch perception.…”
Section: Language-to-music Transfermentioning
confidence: 93%
See 2 more Smart Citations
“…In this period, musical abilities are related to attention, memory, and the acquisition of musical information develop ( Trehub, 2001 ). In addition, language learning has a transfer effect to music learning, and native speakers of different languages have different musical abilities ( Zhang et al, 2020 ). Thus, recruiting subjects from different cultures may be disadvantageous to our study of the influence of training in Chinese and Western music styles on neural plasticity.…”
Section: Introductionmentioning
confidence: 99%